2010
DOI: 10.1002/hep.23723
|View full text |Cite
|
Sign up to set email alerts
|

Carbonyl reductase 1 as a novel target of (−)‐epigallocatechin gallate against hepatocellular carcinoma†

Abstract: Human carbonyl reductase 1 (CBR1) converts the antitumor drug and anthracycline daunorubicin (DNR) into the alcohol metabolite daunorubicinol (DNROL) with significantly reduced antitumor activity and cardiotoxicity, and this limits the clinical use of DNR. Inhibition of CBR1 can thus increase the efficacy and decrease the toxicity of DNR. Here we report that (2)-epigallocatechin gallate (EGCG) from green tea is a promising inhibitor of CBR1. EGCG directly interacts with CBR1 and acts as a noncompetitive inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(43 citation statements)
references
References 30 publications
0
42
1
Order By: Relevance
“…An initial step after infection is thought to be the IRES-dependent translation of the incoming viral RNA. Although the heat shock protein inhibitor quercetin, which is structurally similar to catechins, attenuates HCV production and reduces IRES-dependent translation [13,19], our results indicated that EGCG had no effect on HCV IRES-directed translation (Fig. 6B).…”
Section: Discussioncontrasting
confidence: 58%
“…An initial step after infection is thought to be the IRES-dependent translation of the incoming viral RNA. Although the heat shock protein inhibitor quercetin, which is structurally similar to catechins, attenuates HCV production and reduces IRES-dependent translation [13,19], our results indicated that EGCG had no effect on HCV IRES-directed translation (Fig. 6B).…”
Section: Discussioncontrasting
confidence: 58%
“…45 Hence, this green tea polyphenol may reverse DOX-induced intracellular Ca 2þ depletion and contribute to the maintenance of contractile function. EGCG could also reduce cardiotoxicity induced by daunorubicin (DNR), as shown by Huang et al 17 The proposed underlying mechanism was EGCG inhibition of CBR1, the protein involved in the conversion of DNR into DNROL. DNROL is directly associated with DNR-induced cardiotoxicity thus contributing to limit the use of this drug.…”
Section: Cardiotoxicitymentioning
confidence: 99%
“…In rat, individual catechins and/or green tea extract exhibited protective effects against DOX-induced cardiovascular abnormalities (16), cardiomyocyte injury (17, 18), brain toxicity (19), and spermatogenic disorders (20). Moreover, catechins are able to inhibit carbonyl reductase 1, the main DOX deactivation enzyme (21), and in this way they enhanced DOX efficacy in tumor-bearing mice (22). On the other hand, antioxidant properties of catechins could decrease DOX--mediated oxidative stress in cancer cells, which is believed to contribute to DOX antiproliferative effect (8,12).…”
mentioning
confidence: 99%